Pengembangan Kapasitas Laboratorium Lingkungan dalam Rangka Optimalisasi Pelayanan Publik (Suatu Studi di UPTD Laboratorium Lingkungan Dinas Lingkungan Hidup Kabupaten Pasuruan) - Titisari, Catur; Suryono, Agus; Saleh, Choirul (Badan Penerbitan Jurnal (BPJ) FIA-UB, 2018)
This study uses a qualitative approach, which aims to describe the implementation and results of capacity development in the framework of public services at the UPTD Laboratorium Lingkungan, using the dimensions of Grindle (1997). The result of this study indicate that the UPTD Laboratorium Lingkungan carries out under dimensions, human resources, organizational strengthening and institutional reform. Capacity building is an increase in competence, availability of facilities and infrastructure, organizational structure. Supporting factor of the capacity building of this environmental laboratory are developing industrialization in Pasuruan regency, strengths and weaknesses recognation, leadership support and joint commitment, and concern among members. On the other hand, the inhibiting factors are the number of human resources, budget, and chanes in government policies.